A stakeholder co-design approach to designing a dental service for adults experiencing homelessness - Cairns, Declan; Rodriguez, Andrea (Frontiers in Oral Health, 2024)
IntroductionThe homeless population faces a “cliff edge of inequality” when trying to access essential dental services. There are several additional barriers to accessing dental care in comparison to the general population and the heterogeneous nature of patients presents a significant challenge when designing dental services to meet their needs. Following the Smile4Life report in 2009, there is limited up-to-date and population-specific evidence available for the optimal model of service delivery.AimThis study aimed to co-design principles for a prospective dental service for adults experiencing homelessness.MethodsA qualitative methodology was used to incorporate experts-by-experience into elements of co-designing a dental service for adults experiencing homelessness. The study combined elements of an experienced-based co-design framework for healthcare innovation with community-based participatory research. Focus groups with people experiencing homelessness and healthcare practitioners were conducted to identify principles for any prospective dental service, as well as several barriers and enablers to establishing a homeless dental service. The findings were transcribed and analysed using thematic analysis on Nvivo software.ResultsFrom the qualitative analysis five key themes emerged: (1) Impact and expectations of oral health while experiencing homelessness, (2) Barriers to accessing dental care; (3) Practitioner's views about homelessness and access to care; (4) Barriers to designing a homeless service and (5) Enablers for co-designing a new model of dental care delivery for the homeless population.Five key principles for a new model of homeless dental service were identified: (i) Services designed to address the needs of patients; (ii) Services delivered in a safe and welcoming environment (iii) Training and consistency of staff; (iv) Focus on dental education (v) Developing peer mentoring and peer support.ConclusionWhile the barriers to accessing dental care while homeless are well established and understood by healthcare practitioners, more work is required to gain consensus on the most effective way to deliver an innovative a sustainable dental service for patients experiencing homelessness. Previous negative experiences, lack of readily available information on services and barriers to access in the current system could be addressed by developing peer mentors within the homeless community, empowering individuals to share their knowledge and skills to support others in improving their oral health.